2019
DOI: 10.3389/fonc.2019.00907
|View full text |Cite
|
Sign up to set email alerts
|

Bexarotene Reduces Production of CCL22 From Tumor-Associated Macrophages in Cutaneous T-Cell Lymphoma

Abstract: Bexarotene is a third-generation retinoid X receptor-selective retinoid that has been approved for use in the treatment of both early and advanced cutaneous T-cell lymphoma (CTCL). Although bexarotene has been used for decades in the treatment of CTCL, little is known about the mechanisms underlying its anti-tumor effects in CTCL patients. This study therefore focused on the immunomodulatory effects of bexarotene in vivo using an EL4 mouse T-cell lymphoma model, followed by investigation in CTCL patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 27 publications
1
63
0
Order By: Relevance
“…In addition, Th2 cytokines are known to stimulate the secretion of CCL18 and CCL22 from antigen-presenting cells ( Vulcano et al, 2001 ; van Lieshout et al, 2006 ; Tsicopoulos et al, 2013 ; Furudate et al, 2016 ). These chemokines are indeed expressed by macrophages and DCs in CTCL skin lesions and the levels of CCL18 correlate with those of IL-4 ( Gunther et al, 2011 ; Miyagaki et al, 2013 ; Tanita et al, 2019 ; Vieyra-Garcia et al, 2019 ). A recent study provided evidence suggesting that lesional c-Kit + DCs recruit benign Th2 cells via secretion of CCL18 which leads to formation of an inflammatory synapse between the DCs, benign Th2 cells and the malignant T cells ( Vieyra-Garcia et al, 2019 ).…”
Section: Changes In the Malignant Cytokine Expression Foster A Th2-bimentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, Th2 cytokines are known to stimulate the secretion of CCL18 and CCL22 from antigen-presenting cells ( Vulcano et al, 2001 ; van Lieshout et al, 2006 ; Tsicopoulos et al, 2013 ; Furudate et al, 2016 ). These chemokines are indeed expressed by macrophages and DCs in CTCL skin lesions and the levels of CCL18 correlate with those of IL-4 ( Gunther et al, 2011 ; Miyagaki et al, 2013 ; Tanita et al, 2019 ; Vieyra-Garcia et al, 2019 ). A recent study provided evidence suggesting that lesional c-Kit + DCs recruit benign Th2 cells via secretion of CCL18 which leads to formation of an inflammatory synapse between the DCs, benign Th2 cells and the malignant T cells ( Vieyra-Garcia et al, 2019 ).…”
Section: Changes In the Malignant Cytokine Expression Foster A Th2-bimentioning
confidence: 95%
“…DCs in CTCL skin lesions and the levels of CCL18 correlate with those of IL-4 (Gunther et al, 2011;Miyagaki et al, 2013;Tanita et al, 2019;Vieyra-Garcia et al, 2019). A recent study provided evidence suggesting that lesional c-Kit + DCs recruit benign Th2 cells via secretion of CCL18 which leads to formation of an inflammatory synapse between the DCs, benign Th2 cells and the malignant T cells (Vieyra-Garcia et al, 2019).…”
Section: Changes In the Malignant Cytokine Expression Foster A Th2-bimentioning
confidence: 99%
“…Notably, there was no increase of CCL22 mRNA expression. Since CCL22 is reported to correlate with the progression of CTCL, 6 etoposide might be an ideal drug for immunomodulation of the CTCL microenvironment. Since mogamulizumab is cytotoxic against CCR4+ lymphoma cells by ADCC that depends on the contact between lymphoma cells and effector cells, increased levels of CCL17, CXCL5, and CXCL10 might enhance the therapeutic effect of mogamulizumab.…”
Section: Discussionmentioning
confidence: 99%
“…We found that CCL17, as well as the other CCR4 ligand, CCL22, strongly correlated with mSWAT, with a more pronounced effect observed in lesional blood than in peripheral blood (Figure 3d). The serum level of CCL22 reportedly decreases following treatment with bexarotene 17 . In this study, bexarotene combined with phototherapy caused a decrease in CCL22 levels in lesional blood, but not in peripheral blood ( Figure 6d, e).…”
Section: Detailed Chemokine Profile Of Lesional Bloodmentioning
confidence: 96%